My Big Boy Potty - Joanna Cole (New York, NY, United States HarperCollins Publishers Inc, 2007)
"What a big boy you are!" Potty training can be fun. With warmth and sensitivity, Joanna Cole and Maxie Chambliss guide young boys though the challenges and rewards potty training-from the first steps to the joy of graduating to big boy underpants! A helpful "Note to parents" is included.
Keywords: Read Aloud -- Read Aloud